Hubungan Mutu Pelayanan Rekam Medis Dengan Kepuasan Pasien di Puskesmas X Tahun 2023 - Joni Herman; Rudiansyah Rudiansyah; Uray Bilchairi Jakti (HB PRESS, 2023)
Quality medical records are health services aimed at patients as effectively as possible according to the latest knowledge. Responsiveness refers to the ability to assist customers in providing timely and accurate service. Based on data, the percentage of patients who received services at Puskesmas X in 2020 was 72%, compared to the national average of 90%. Based on data collected from 15 participants, 40% of them said they were not sure about the results, while 60% said they were confident about the results. The goal was to understand the relationship between the quality of medical staff training and the readiness of new employees. Quantitative research design combined with cross-sectional design. The number of respondents was approximately 1,147 people and the sample members were 297 people. The research technique is called Accidental Sampling. The results of the analysis of respondents show that around 67.7% and 32.3% of them are women. Meanwhile, responsiveness ranged from 45.1% good to 54.9% poor.